Assessing the effect of regional deprivation on mortality avoiding compositional bias: a natural experiment - Reiss, Katharina; Berger, Ursula; Winkler, Volker; Voigtländer, Sven; Becher, Heiko; Razum, Oliver (Journal of epidemiology and community health, 2013)
Background and objective We assessed the effect of regional deprivation on individual mortality by making use of a natural experiment: we followed up ethnic German resettlers from Former Soviet Union countries who were quasi-randomly distributed across the socioeconomically heterogeneous counties of Germany's federal state North Rhine-Westphalia (NRW). - Methods We used data from the retrospective cohort study ‘AMOR’ on the mortality of resettlers in NRW (n=34 393). Based on the postcode of the last known residence we linked study participants to the 54 counties of NRW, which were aggregated in six deprivation clusters. Mortality rates and standardised mortality ratios (SMRs) were calculated for each cluster. After a mean follow-up of 10 years, 2580 resettlers were deceased. - Results For male and female cohort members, mortality rates and SMRs were highest in the cluster ‘poverty poles’ (SMR men: 1.21, 95% CI 1.04 to 1.41; SMR women: 1.17, 95% CI 0.99 to 1.37), whereas they were lowest in the cluster ‘prospering regions and suburban counties’ (SMR women: 0.86, 95% CI 0.70 to 1.05) as well as in the cluster ‘heterogeneous counties’ (SMR men: 0.73, 95% CI 0.61 to 0.88). - Conclusions The population which was quasi-randomly distributed to counties of differing socioeconomic status experienced different levels of mortality. It was highest in regions with the highest level of regional deprivation. Previous studies describing this positive relationship between mortality and regional deprivation could not differentiate between compositional and contextual effects. Thus, our findings indicate that in terms of mortality, regional deprivation does matter.
Published online first 23 October 2012
Gesehen am 21.12.2021